ALKBH5 suppresses gastric cancer tumorigenesis and metastasis by inhibiting the translation of uncapped WRAP53 RNA isoforms in an m6A-dependent manner - Ziqi Zheng; Feizhi Lin; Baiwei Zhao; Guoming Chen; Chengzhi Wei; Xiaojiang Chen; Runcong Nie; Ruopeng Zhang; Zhoukai Zhao; Zhiwei Zhou; Yuanfang Li; Weigang Dai; et al. (Molecular Cancer)
Abstract The N6-methyladenosine (m6A) modification serves as an essential epigenetic regulator in eukaryotic cells, playing a significant role in tumorigenesis and cancer progression. However, the detailed biological functions and underlying mechanisms of m6A regulation in gastric cancer (GC) are poorly understood. Our research revealed that the m6A demethylase ALKBH5 was markedly downregulated in GC tissues, which was associated with poor patient prognosis. Functional studies demonstrated that suppressing ALKBH5 expression enhanced GC cell proliferation, migration, and invasion. Mechanistically, ALKBH5 removed m6A modifications from the 5’ uncapped and polyadenylated transcripts (UPTs) of WRAP53. This demethylation decreased WRAP53 stability and translation efficiency. The lower level of WRAP53 disrupts the interaction between USP6 and RALBP1 protein, promoting RALBP1 degradation and thereby suppressing the PI3K/Akt/mTOR signaling cascade, ultimately attenuating the progression of GC. These findings highlight the pivotal role of ALKBH5-mediated m6A demethylation in inhibiting GC progression and the potential role of ALKBH5 as a promising biomarker and therapeutic target for GC intervention.